Предмет: Математика,
автор: 456783790
Помогите пожалуйста
Приложения:
Ответы
Автор ответа:
0
Ответ:
Д)-15
Пошаговое объяснение:
(-99аб*3,9) / (1,3*(-6,6)*(-3аб))=
=(-1*11*3*3*аб*1,3*3) / (1,3*(-1)*11*3*2*0,1*(-1)*3*аб)=
=( -1*11*3*аб*1,3*3 )(3) / (-1*11*3*аб*1,3*3 )(-2*0,1)=
=(3)/(-2*0,1)=(3*10)/(-2*0,1*10)=30/(-2)=-(30/2)=-15
Похожие вопросы
Предмет: История,
автор: Alinashmidt2345
Предмет: Информатика,
автор: Gitersexminator
Предмет: Алгебра,
автор: Аноним
Предмет: Математика,
автор: volselectric
Предмет: Физика,
автор: mahatkala121212